Impaired memory by hippocampal oxidative stress in rats exposed to 900 MHz electromagnetic fields is ameliorated by thymoquinone - ÜSTÜNOVA, SAVAŞ; ÜSTÜNOVA, SAVAŞ; KILIÇ, AYSU; KILIÇ, AYSU; Bulut, Huri; Gurel-Gurevin, Ebru; ERİŞ, ALİ HİKMET; ERİŞ, ALİ HİKMET; MERAL, İSMAİL; MERAL, İSMAİL (My University, 2022)
The protective effects of thymoquinone on learning and memory abilities and on hippocampal oxidative stress in rats exposed to 900 MHz electromagnetic field radiation at s strength of 6.0 +/- 0.5 V/m for 1 h on each of 15 days was studied. Thymoquinone-treatment (10 mg/kg/day) of radiation-exposed rats resulted in better performance than that of radiation-exposed rats not receiving thymoquinone. Electromagnetic field-exposure led to increased hippocampal superoxide dismutase, glutathione peroxidase, and malondialdehyde levels and to lowered brain-derived neurotrophic factor level; thymoquinone treatment ameliorated all four parameters. Also, in the electromagnetic field-exposed group, N-methyl-D-aspartate receptor expression decreased, and gamma-aminobutyric-acid alpha receptor expression increased, which was reversed by thymoquinone treatment. In conclusion, treatment with the thymoquinone ameliorated the impact of the exposure to EMF and provided a hint on the mechanism involving oxidative stress.